Treningsmotivasjon og fysisk aktivitet blant unge: - Arntsen, Camilla; Kobbeltvedt, Therese (Nordisk Tidsskrift for Helseforskning, 2012)
Motivation for physical activity and amount of physical activity amongst adolescents: What differences exist between active and inactive groups of Norwegian adolescents with reference to demography, Body Mass Index (BMI), subjectively perceived health, motivation for physical exercise, and initiative? Abstract This study is based on the Norwegian data from the HEVAS (Helsevaner blant barn og unge) WHO-survey. We investigated: What differences exist between active and inactive groups of individuals with reference to demography, Body Mass Index (BMI), subjectively perceived health, motivation for physical exercise, and initiative? Compared to inactive individuals, physically active individuals reported higher socioeconomic status, lower BMI, better subjectively perceived health. The active individuals report more health motivation than the inactive individuals. Of all the factors included in this study, initiative was the one differentiating the groups. Active individuals report more initiative than inactive individuals.